Philip Roth and the American Liberal Tradition since FDR - Connolly, Andrew (The University of Edinburgh, 2012)
This thesis takes as its focus several works in the late period of Philip Roth’s writing and examines the way in which these particular texts address issues of American national experience since the Depression. In particular, this study looks at Roth’s assessment of a distinctly modern liberal vision that came to prominence during the 1930s and was to dominate American political and cultural life until the late 1960s. In thus covering the wider historical sweep of these novels, the research will draw attention to the way in which such broader matters of American cultural and political life intersect with more local issues of Jewish-American subjectivity and literary style that have been explored recurrently throughout Roth’s greater body of fiction. This study thus aims to show how the more recent ‘historical turn’ in Roth’s novelistic focus is in fact consistent with certain pivotal themes that have helped to define his overall development as a writer.
Keywords: Roth, Philip; American fiction; American liberalism